If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9(4x + -2) = 108 + -6x Reorder the terms: -9(-2 + 4x) = 108 + -6x (-2 * -9 + 4x * -9) = 108 + -6x (18 + -36x) = 108 + -6x Solving 18 + -36x = 108 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 18 + -36x + 6x = 108 + -6x + 6x Combine like terms: -36x + 6x = -30x 18 + -30x = 108 + -6x + 6x Combine like terms: -6x + 6x = 0 18 + -30x = 108 + 0 18 + -30x = 108 Add '-18' to each side of the equation. 18 + -18 + -30x = 108 + -18 Combine like terms: 18 + -18 = 0 0 + -30x = 108 + -18 -30x = 108 + -18 Combine like terms: 108 + -18 = 90 -30x = 90 Divide each side by '-30'. x = -3 Simplifying x = -3
| 4(2x+2)=7x+1 | | 6x+3x-x=96 | | 2c-11c+5=0 | | 2(m-3)=2(m-6) | | 5x^2-30x+100=0 | | 4(-5-x)=10-2x | | -.25x-9=.90 | | 8-h=-4 | | .28=.04(w-1.0) | | -4-6x=20 | | .28=.04(w-10) | | (3x^3)-(2x^2)= | | 0.4x-3.4=46 | | -.25-9=.90 | | 2x+11=3x+4 | | 3x^3-2x^2= | | -6m+69-9(m+1)=4m-(2m-2)-7m+6 | | 1170=68 | | (X^2+x-6)(x^2+x-2)+3= | | 0.50h-7=15 | | 9f+5(-8+3f)= | | 2[t-(2t+18)+15]=2(t+3) | | 4x+235=12x-5 | | (k,k+14)=0 | | 7y+8=1 | | 4m=12 | | 0.65x+.05(8-x)=.10(76) | | -28p-6(3-6p)=6(p-4)-2 | | 400x-100(30-x)=0 | | 8x^2-7x+4=-3x+2 | | 3x+41-6x=2-9x+3 | | t+23=15 |